ComB proteins expression levels determine Helicobacter pylori competence capacity - Corbinais, Christopher (2017)
Helicobacter pylori chronically colonises half of the world's human population and is the main cause of ulcers and gastric cancers. Its prevalence and the increase in antibiotic resistance observed recently reflect the high genetic adaptability of this pathogen. Together with high mutation rates and an efficient DNA recombination system, horizontal gene transfer through natural competence makes of H. pylori one of the most genetically diverse bacteria. We show here that transformation capacity is enhanced in strains defective for recN, extending previous work with other homologous recombination genes. However, inactivation of either mutY or polA has no effect on DNA transformation, suggesting that natural competence can be boosted in H. pylori by the persistence of DNA breaks but not by enhanced mutagenesis. The transformation efficiency of the different DNA repair impaired strains correlates with the number of transforming DNA foci formed on the cell surface and with the expression of comB8 and comB10 competence genes. Overexpression of the comB6-B10 operon is sufficient to increase the transformation capacity of a wild type strain, indicating that the ComB complex, present in the bacterial wall and essential for DNA uptake, can be a limiting factor for transformation efficiency.